Eksplorasi STEAM Pada Sarana Upakara Tumpeng Kering - Kadek Rahayu Puspadewi; I Gusti Ayu Putu Arya Wulandari Wulandari; Anak Agung Inten Paraniti; Ni Komang Safitri (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
Dried tumpeng is one of the traditional ceremonies used by Hindus in Bali. This study aims to examine the elements of STEAM contained in dried tumpeng. This research is a qualitative descriptive study with an ethnographic design. The subject of this research is the community of entrepreneurs of dried tumpeng in Guwang Village, Sukawati District, Gianyar. The data in this study were obtained through interviews, observation, and documentation. The data was then analyzed in three stages, namely data reduction, data presentation, and data conclusion. To get valid and objective data, triangulation method is used. The results showed that there were STEAM elements in the process of making dried tumpeng, namely the scientific element can be seen from the coloring process, adhesives and drying techniques used, the technological element can be seen from the dried tumpeng printing equipment, the machine element can be seen from the design of the printing equipment used, the art element can be seen from the various colors of the dried tumpeng, and the mathematical element can be seen from the raw production costs, income, sales, losses, and the comparison of the materials used. These STEAM elements can be used in social arithmetic learning. Students can be asked to make a project of making dried tumpeng  from the beginning of manufacture, packaging to even the sales stage so that learning can be more meaningful. Keywords: Dried tumpeng, STEAM